PERSEPSI PASANGAN USIA SUBUR (PUS) DALAM MEWUJUDKAN NKKBS DI NAGARI TANDIKEK KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN - Rosalina, Nadia Jeni; Erita, Yeni; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
This study aimed to obtain the data, process, analyze and discuss the study in achieving PUS Tandikek NKKBS in Nagari Padang Pariaman District Sub Patamuan views of: 1) Knowledge, 2) participation, 3) family planning counseling. This study considered the descriptive research. The study population was all the PUSs in Nagari Tandikek Patamuan Pariaman District district. Samples were taken with a proportional random sampling technique with the proportion of 10% of the population in the study area, the study sample, 92 members of PUS. Guided data collection using questionnaires, statistical analysis used is descriptive by using a percentage formula. The results showed: 1) Lack of knowledge in achieving PUS to NKKBS NKKBS, only 33.69% who knew about Tandikek NKKBS in Nagari Padang Pariaman District Patamuan District, 2) participation in the realization of PUS NKKBS very less only 33.69%, although Participation KB is a good range to 79.35% in Tandikek Nagari Padang Pariaman District Patamuan District, PUS implement family planning programs just for kids imprison not to realize NKKBS, 3) lack of participation in the PUS to realize NKKBS family planning counseling, only 33.69% in Tandikek Nagari Padang Pariaman District Patamuan district.